Pemanfaatan Aeromonas hydrophila Untuk Mengendalikan Penyakit Layu Fusarium Pada Beberapa Varietas Sorgum Manis (Sorghum bicolor (L.) Moench - ARIAWAN, I WAYAN GENTA; SUPRAPTA, DEWA NGURAH; SUNITI, NI WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2015)
The Use of Aeromonas hydrophila to C ontrol Fusarium Wilt Disease on S everal V arieties of S weet S orghum ( Sorghum bicolor ( L.) Moench ) Objective of this study was to test the effectiveness of A. hydrophila to control wilt disease caused by Fusarium sp. on several varieties of sweet sorghum. Results of this study showed that application of rhizobacteria affected the growth and the yield of sweet sorghum. Under in vitro condition, treatments with A. hydrophila isolate KtBlt2 could suppress the growth of the Fusarium sp. with inhibitory activity 76.06% when compared to control. Under field condition treatment P6 (treatment wilt A. hydrophila on variety FS-501) could suppress Fusarium wilt disease with the lowest disease incidence by 3.24%. It is necessary to test the stability of A. hydrophila as biocontrol agent against Fusarium sp. Keywords : A. hydrophila , Fusarium sp . , sweet sorghum